The future of the IMF: how to prevent the next global financial crisis - Horst Siebert (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
The paper analyzes how the next financial crisis can be prevented and which role the IMF should play. The paper distinguishes between the improvement of existing instruments and solving the moral hazard problem. Both issues are interrelated. The size of operation of the IMF creates a moral hazard problem. The IMF should credibly announce the ex-post rules for bridging a liquidity gap in order to set the right ex-ante incentives for the behavior of debtors and creditors. An institutional design for dealing with private and sovereign debt analogous to national bankruptcy rules has to be developed.
Keywords: F00; F02; F33; F34; 330; Internationales Währungssystem; Internationaler Kredit; Moral Hazard; Währungskrise; Anpassungsprogramm des IWF; Glaubwürdigkeit; Welt